Effects of Management, Dietary Intake, and Genotype on Rumen Morphology, Fermentation, and Microbiota, and on Meat Quality in Yaks and Cattle - Hu, Changsheng; Ding, Luming; Jiang, Cuixia; Ma, Chengfang; Liu, Botao; Li, Donglin; Degen, Abraham Allan (Frontiers in Nutrition, 2021)
Yaks traditionally graze only natural grassland, even in harsh winters. Meat from grazing yak is considered very healthy; however, feedlot fattening, which includes concentrate, has been introduced. We questioned whether this change in management and diet would have an impact on the rumen and meat quality of yaks. The current study examined the morphology, fermentation and microbiota of the rumen and the meat quality of three groups of bovines: 1) grazing yaks (GY, 4-year old), without dietary supplements; 2) yaks (FY, 2.5-year old) feedlot fattened for 5 months after grazing natural pasture; and 3) feedlot fattened cattle (FC, Simmental, 2-year old). Ruminal papillae surface area was greater in FY than in GY (P=0.02) and ruminal microbial diversity was greater but richness was lesser in GY than in FC and FY. Both yak groups had higher protein and lower fat contents in meat than FC. Meat of GY had a lower n6:n3 ratio than FY and FC, and was the only group with a ratio below 4, the recommended value for healthy food. Essential amino acids (EAA), as a proportion of total AA and of non-essential AA of yak meat met WHO criteria for healthy food; whereas FC did not.